It takes two to tango - how teacher-child interactions help advance children’s emotion knowledge - Hormann, Oliver; Voltmer, Katharina; von Salisch, Maria (Frontiers in Psychology, 2025)
Because young children’s emotion knowledge and language skills grow in tandem and contribute to their success in school, the Feeling Thinking Talking (FTT) teacher training, which addresses both areas, was developed. In this training, preschool and kindergarten teachers were taught to use language support strategies (LSSs) and responsive child-directed speech when talking about emotions with the children in their care. Whether these educational practices in teacher–child talk improve children’s emotion knowledge was examined with N = 275 children (Mage = 49.86 months, SD = 7.21, range = 35–66 months at t1) who were cared for by teachers in N = 16 training classrooms and N = 13 waitlist-control classrooms, which were nested in 13 centers. Children were individually tested on morphology, grammar, and emotion knowledge (EK) before (t1) and after the FTT training (t2). At t1 and t2, teacher–child interactions were videotaped and coded. Single-level models suggest that training group teachers used LSSs (input-oriented strategies and stimulation techniques) more often and involved children in longer dialogues than control group teachers at t2. Multilevel models show that dialogue length and feedback strategies at t1 and input-oriented strategies at t2 contributed to the explanation of gains in children’s EK over time (after controlling for covariates). Moreover, teachers’ use of input-oriented strategies at t2 that improved under the FTT training partially mediated the effect of the intervention on children’s EK growth. In addition, children’s (growing) language skills seem to mediate the effects of these educational practices on their EK. Ways in which educational practices affect emotion learning are discussed.